2011
DOI: 10.1136/jech.2010.125500
|View full text |Cite
|
Sign up to set email alerts
|

Explaining socioeconomic differences in adolescent self-rated health: the contribution of material, psychosocial and behavioural factors

Abstract: The findings show that the main explanatory approaches for adults also apply to adolescents. The direct and indirect contribution of material factors for inequalities in self-rated health was stronger than that of behavioural and psychosocial factors. Strategies for reducing health inequalities should primarily focus on improving material circumstances in lower affluent groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0
20

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(114 citation statements)
references
References 44 publications
(24 reference statements)
6
87
0
20
Order By: Relevance
“…Statistics Canada reported that in 2006, 62·9 % of 25-64-yearold adults in Vancouver completed college or university education (46) , which was similar to the student-reported parent education estimated in this sample (63·7 %). Research suggests that individuals living in neighbourhoods with high area-level SES may experience health advantages, even if they live in lower-income households (47) , because of greater local access to health services (47) or the influence of social networks (12,48) . The high level of educational attainment in Vancouver is somewhat paradoxical in a region where the before-tax child poverty rate stands at an estimated 18·4 % (in Metro Vancouver, defined by the Statistics Canada lowincome cut-off) (9) , housed in a province with persistently high child poverty rates (49) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistics Canada reported that in 2006, 62·9 % of 25-64-yearold adults in Vancouver completed college or university education (46) , which was similar to the student-reported parent education estimated in this sample (63·7 %). Research suggests that individuals living in neighbourhoods with high area-level SES may experience health advantages, even if they live in lower-income households (47) , because of greater local access to health services (47) or the influence of social networks (12,48) . The high level of educational attainment in Vancouver is somewhat paradoxical in a region where the before-tax child poverty rate stands at an estimated 18·4 % (in Metro Vancouver, defined by the Statistics Canada lowincome cut-off) (9) , housed in a province with persistently high child poverty rates (49) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that a differential distribution of psychosocial factors may play a role in socio-economic differences in health outcomes (11,12) . Given that SES is a difficult factor to change through health interventions alone, there is a pressing need to identify modifiable factors that mediate associations between SES and dietary outcomes, to serve as pragmatic loci for interventions aimed at reducing socio-economic disparities in nutritional outcomes.…”
mentioning
confidence: 99%
“…It is difficult to compare these data with similar ones, as there is a paucity of literature comparing trends in SRH among adolescents; few studies are concerned with the reliability of the measure of SRH along time, through adolescence 13 and from adolescence through to adulthood 12 and of its relationship with future health. Moreover some others try to relate it cross-sectionally with some background conditions, such as socioeconomic status 15 . Interpreting these trends should therefore be done with much caution and with the help of significant data on the countries condition during this decade.…”
Section: Discussionmentioning
confidence: 99%
“…En este estilo de vida no existe vida interior o espiritualidad. En la actual posmodernidad, la familia natural y la espiritualidad ya no son el eje de la sociedad (13). Por este motivo, la vida humana se ha cosificado en grado sumo.…”
Section: Componentesunclassified